Statistical Modelling of Precipitation of Copper Ammonium Sulphite from Synthetic Copper Sulphate Solutions - Demir, Fatih (Asian Journal of Chemistry, 2014)
Copper ammonium sulphite was precipitated under optimum conditions by passing SO2 from a synthetic aqueous copper sulphate solution. Copper ammonium sulphite, Cu2SO3·(NH4)2·SO3, was characterised by XRD. The effects of parameters such as initial concentration, pH, stirring speed and reaction time were investigated on precipitation. A first-order model was obtained using the 24 full factorial design method. It was observed that all parameters on the precipitation of copper ammonium sulphite were effective. The optimum conditions established for maximum copper precipitation at room temperature were: stirring speed 700 rpm, initial concentration 0.8 mol L-1, pH 3.5 and reaction time 15 min. Under these optimum conditions, the percentage of precipitated copper from solution was 99.80.